KONSEP WAHYU MENURUT SAKSI-SAKSI YEHUWA - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2018)
In the mainstream Christianity, revelation of God manifests in Jesus Christ, in his blood and flesh. Jehovah's Witnesses, as a sect in Christianity, believes that the revelation or word of God is fully Bible, and not Jesus as in the mainstream Christianity. Bible is revealed by God directly so it is accurate. It is also belived as The Book of God's Thought because was written in His guidance. This concept of revelation has serious implications to the dogma of the Trinity. Based on Bible, Jehovah's Witnesses believes that God is not the Trinity, but God is One God and One Person named Jehovah. Jesus also is not part of the Trinity. Indeed Jesus is believed as God's word, but as a speaker of God. He is also believed as the son, as God fiirst creation. by God. Therefore, Jesus is a creature of Jehovah and is not God, so is not part of the Trinity.